Balancing Growth and Sustainability: The Role of Manufacturing and Renewable Energy in CIVETS Countries - Supartoyo, Yesi Hendriani; Wahyudi, Setyo Tri; Firmansyah, Firmansyah; Damayanti, Rosita Mei; Rosdaliva, Mehilda; Martini, Endang; Hatmanto, Tria (International Journal of Energy Economics and Policy, 2026)
This study investigates the relationship between renewable energy consumption, manufacturing value added, CO₂ emissions, and economic growth in CIVETS countries – Colombia, Indonesia, Vietnam, Egypt, Turkey, and South Africa – from 2005 to 2020. Using panel data techniques (common, fixed, and random effects models), the results reveal that manufacturing significantly and positively affects GDP growth, confirming its role as the primary driver of economic performance in emerging economies. Conversely, CO₂ emissions exert a negative but marginal influence on GDP growth, indicating that higher emissions may hinder sustainable economic expansion. Renewable energy consumption, although showing a limited short-term impact, demonstrates potential to contribute to long-term inclusive growth once effectively integrated into industrial structures. These findings emphasize the need for policies promoting green industrial transformation, investment in clean technologies, and enhanced renewable energy integration to achieve balanced growth and environmental sustainability. The study offers empirical evidence to support policy design in emerging economies pursuing the dual objectives of industrial competitiveness and carbon neutrality.